An Integrated method of: Area determination of cross-section - Henari, Kubad Zeki (Sulaimani Journal for Pure and Applied Sciences, 1999)
An integrated method for determination of the areas from cross-sections of one level section, two level section and three level section was followed. The cases of seciton of cut only, fill only and partly cut and partly fill sections with their combinations between different types of cross-sections are considered to be fifty-eight cases. From these cases five main half sections generalize the calculation of the areas and the combination between them recovers all fifty-eight cases of the sections. Calculation of areas was performed using graphs using graphs and tables with simple multiplication and additions.